Neurodevelopmental Outcomes in Children with Down Syndrome and Infantile Spasms - Tapp, Sarah; Anderson, Tovi; Visootsak, Jeannie (Journal of Pediatric Neurology, 2015)
Down syndrome (DS) is the most common genetic cause of intellectual disability in the United States. The prevalence of seizure in individuals with DS is 1 to 13%, and infantile spasm (IS) occurs in 6 to 32% of those with seizures. Since IS is relatively common in children with DS, it is important to understand the impact IS has on the neurodevelopmental outcomes to provide appropriate anticipatory guidance to help maximize the potential of these children. Our study is the first to compare the neurodevelopmental outcomes of children with DS and IS (DS + IS) to children with DS and no history of seizures (DS − IS). Using the Bayley scales of infant and Toddler development III, we assessed the neurodevelopment of 29 subjects (8 DS + IS and 21 DS − IS). Neurodevelopmental outcome was poor in the DS + IS cohort, but the delay in treatment does not appear to contribute to any differences in their developmental scores. However, when compared with children with DS − IS, the DS + IS cohort scored approximately 20 points less in all domains including cognitive, motor, and language (p < 0.05). Our results indicate that IS may impact the neurodevelopmental outcomes of children with DS + IS; thus, it is important to provide ongoing developmental and educational assessments and potentially additional therapies for children with DS + IS.
Keywords: Down syndrome; infantile spasms; neurodevelopmental outcomes